2008
DOI: 10.1021/jp800782e
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Computational Methods for Accurately Predicting Reduction Potentials of Organic Molecules

Abstract: A simple computational approach for predicting ground-state reduction potentials based upon gas phase geometry optimizations at a moderate level of density functional theory followed by single-point energy calculations at higher levels of theory in the gas phase or with polarizable continuum solvent models is described. Energies of the gas phase optimized geometries of the S0 and one-electron-reduced D0 states of 35 planar aromatic organic molecules spanning three distinct families of organic photooxidants are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
63
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(72 citation statements)
references
References 28 publications
6
63
1
Order By: Relevance
“…The calculated R value seems to give a good heuristic for anesthetic action and correctly predicts the high anesthetic potencies of Xe, barbital, etomidate, alfaxalone, and cyclopropane and the nonanesthetic nature of fluothyl and DMFPC. SF 6 is clearly anomalous, maybe because DFT methods, although generally accurate when calculating HOMO energies (87), are known to miscalculate SF 6 by several electronvolts (88). The other results are in general agreement with the Meyer-Overton relationship and its best-documented exceptions.…”
Section: Discussionsupporting
confidence: 60%
“…The calculated R value seems to give a good heuristic for anesthetic action and correctly predicts the high anesthetic potencies of Xe, barbital, etomidate, alfaxalone, and cyclopropane and the nonanesthetic nature of fluothyl and DMFPC. SF 6 is clearly anomalous, maybe because DFT methods, although generally accurate when calculating HOMO energies (87), are known to miscalculate SF 6 by several electronvolts (88). The other results are in general agreement with the Meyer-Overton relationship and its best-documented exceptions.…”
Section: Discussionsupporting
confidence: 60%
“…Given the computational cost savings of our present method only requiring a single closed‐shell calculation, the added cost of a single CPCM calculation can generally easily be absorbed and is advisable wherever feasible. It was also observed that the root mean square deviation for individual families was in general just slightly better than for the global correlations (Supporting Information), indicating that when a correlation is available for an exact family of molecules, the correlation is particularly good for that family; however, the almost equally good global correlations clearly indicate that good predictive ability should be able to be obtained even for molecules not necessarily well represented structurally in the initial correlation, just as the Gillmore group noted for their prior method …”
Section: Resultsmentioning
confidence: 99%
“…The correlations in Tables and were built with the experimental reduction potentials on the x ‐axis, because this was the control variable as the correlations were built and also to be consistent with our previous work the energy difference between the initial closed‐shell singlet and one‐electron reduced doublet states was used as an analog to an electron affinity in a dielectric continuum rather than the gas phase.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations